Diplomasi Indonesia Kepada WHO Terkait Penanggulangan Gangguan Penglihatan 2016-2020 - Dhia Arnaz (2022)
Abstract Eyes are one of the main senses that people have. If you cannot see, your daily life would be disrupted. Many people doesn't aware of the importance of it. Vision impairment may cause blindness and effects activities of our daily routine. There are so many countries that has high vision impairment, including Indonesia. Therefore, Indonesia conducted diplomacy resolution to WHO regarding prevention of vision impairment. The intention is to reduce vision impairment in the world. Then it can be integrate the service of vision impairment in order to be prevented or treated properly The researcher discusses how the diplomacy process carried out by Indonesia to the WHO as an international organization that addresses health problems in dealing with visual impairments. The author uses the theory of international organizations, the theory of diplomacy, and also global health diplomacy because these concepts and theories are the basis for the submission of the resolution. In addition, these theories are used to analyze the diplomatic process carried out by Indonesia to the WHO regarding the prevention of visual impairment. The researcher uses qualitative research methods because this research describes the stages in conducting multilateral diplomacy, which involves many countries as well as international organizations. Then the researchers also carried out data collection techniques using interview techniques. This research resulted in an "Eye Health" resolution entitled "Integrated People-Centred Eye Care, including Preventable Vision Impairment and Blindness". During the submission of the resolution, there were several stages, challenges, and obstacles that were felt by Indonesia in order to achieve the "Eye Health" resolution. Keywords: Diplomacy, Indonesia, WHO, Visual Impairment